Pengaruh pendekatan pembelajaran problem solving model polya terhadap kemampuan pemecahan masalah matematis siswa kelas VIII SMP Muhammadiyah Rambah - Kartini, Hartik A'afiyati; Ario, Marfi; Sari, Riska Novia (Jurnal Pendidik Indonesia, 2020)
The low mathematical problem-solving abilities of students are due to teacher-centered learning and a lack of independent study habits. This study aims to examine the effect of Polya's problem-solving approach on the mathematical problem-solving abilities of eighth-grade students at SMP Muhammadiyah Rambah. This research is a quasi-experimental study using the Non-Equivalent Posttest-Only Control Group Design. The population consists of all eighth-grade students at SMP Muhammadiyah Rambah. Samples were selected using random sampling, resulting in class VIII-1 as the experimental group and class VIII-2 as the control group. The experimental group used Polya's problem-solving approach, while the control group received conventional instruction. Data on mathematical problem-solving abilities were collected through tests administered at the end of the learning process, using validated instruments that measured validity, difficulty level, discrimination power, and reliability. Data analysis included hypothesis testing, preceded by a normality test. The normality test results indicated that the data were not normally distributed, so the Mann Whitney test was used for hypothesis testing. The results showed that Zcount = 4.95 > Ztable = 1.96 with α = 0.05, leading to the rejection of H0. Therefore, it can be concluded that Polya's problem-solving approach significantly affects the mathematical problem-solving abilities of eighth-grade students at SMP Muhammadiyah Rambah.